Phylogeny of Australian Acerentomidae species (Protura: Acerentomidae), with a key to identification - Shrubovych, Julia; D’haese, Cyrille (Zootaxa, 2024)
The materials of three Acerentomidae species from Australia and Tasmania were studied. Additional morphological characters, such as chaetotaxy of head and notal segments, shape of body setae and porotaxy, are provided based on new materials of Australentulus westraliensis from Australia and Tasmanentulus tasmanicus from Tasmania. A new species, Amphientulus markstivensi, is described from Tasmania. The steps of reduction of morphological characters along the presumed phylogenetic line Acerentulus – Australentulus – Tasmanentulus – Amphientulus are discussed. The apical tuft of setae on the labial palps is reduced in Australentulus, Tasmanentulus and Amphientulus. In Tasmanentulus and Amphientulus there is also a reduction of setal number to two setae on abdominal legs. Phylogenetic relationships within Australian Acerentomidae genera are discussed. An identification key to Australian Acerentomidae species is provided.